Respiratory characteristics of Hoplostenum littorale (Siluriformes, Callichthyidae) - Affonso, Elizabeth Gusmão (Acta Amazonica, 2001)
Hematological parameters, intraerythrocytic phosphates, hemoglobin, and whole blood Bohr effect of the South American armored catfish Hoplostenum littorale were studied during different seasons of the year. In addition, the degree of dependence on air breathing was determined for this species. The hematological parameters presented seasonal variations, which were not correlated to oxygen, temperature, and water level oscillations. Five anodic hemoglobin fractions were detected in starch gel electrophoresis. In addition to ATP, GTP and Fe-GTP being detected, 2,3-DPG was also detected in red blood cells of H. littorale. The latter is an intraerythrocytic phosphate characteristic to red blood cells of mammalians. The increased production of 2,3-DPG could be associated with decreasing Hb-O2 affinity and both features could be related to environmental temperature increase. Whole blood Bohr effect was influenced by water temperature. This study confirms H. littorale to be continuous and not obligate air breather, under all dissolved oxygen level conditions.
Características respiratórias de Hoplostenum littorale (Siluriformes, Callichthyidae)
Keywords: Adaptation; Air-breathing Behavior; Hematology; Intraerythrocytic Phosphate; Blood Bohr Effect; Adaptação; Comportamento Da Respiração Aérea; Hematologia; Fosfatos Intraeritrocitários; Efeito Bohr Do Sangue